(untitled) (Scientia Agropecuaria, 2020)
Peru is the second-largest rice producer in Latin America, with 406166 ha grown annually, predominately on the Peruvian north coast. However, rice is primarily irrigated by flooding (93%), which demands high water use (15000-18000 m3 ha−1) owing to low water-use efficiency. Additionally, the intensification of climate change is of great concern as it causes high variability as well as a decreasing trend in water resource availability. Alternate wetting and drying (AWD) irrigation technique reportedly reduce the irrigation volumes while maintaining conventional yield rates. The AquaCrop model was calibrated and assessed to simulate rice yield response to the AWD technique under water shortage conditions on the Peruvian central coast. The AquaCrop model exhibited a “very good” to “good” performance in predicting canopy cover development, soil water content, aerial biomass, and grain yield using performance indicators, such as the Nash-Sutcliffe efficiency coefficient, the RMSE observations standard deviation ratio (RSR), Willmott index, and determination coefficient. The calibrated model showed a good performance of rice under AWD irrigation, indicating that this technique can be used to assess rice production under Peruvian arid conditions.